A Cooperative System of GIS and BIM for Traffic Planning: A High-Rise Building Case Study - Wang, Jun; Hou, Lei; Chong, Heap Yih; Liu, Xin; Wang, Xiangyu; Guo, J. (Springer, 2014)
Design of localized traffic is a decision-making process for producing the viable solutions of where the parking lots, roads, entrances, exits, and the associated facilities should be built. In a traditional design case, a planner may take into account numerous factors, such as economy, constructability, geological impacts, layout constraints, connection of localized and external traffic, etc., and the process is mainly relied on a master plan and two-dimensional design drawings. Such pattern has certain limitations as these important factors can hardly be overall considered at the same time. It is promising to cope with the issues using a cooperative system where Geographic Information System (GIS) incorporates with Building Information Modelling (BIM). The research aims to optimize and evaluate the site layout for effective traffic planning based on the integrative approach of BIM and GIS. From the case study, the paper also demonstrates: 1) the approach of analyzing the statistical data to represent the existing traffic condition around the building via GIS and 2) the approach of making use of the advanced vehicle simulation models to optimizing the localized traffic facilities design, considering the possible impact of the localized traffic to the ambient traffic. Referring to the cooperative system, the bottlenecks of the initial design of parking facilities are identified, and the corresponding improvements are suggested.